2020
DOI: 10.13189/azb.2020.080506
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastrointestinal Helminth Parasites in Gallus gallus domesticus in Lucknow, U. P, India

Abstract: Poultry industry occupies an important position in the provision of animal protein and plays a vital role in the national economy. Helminthiasis caused by helminth parasites is one of the most common infections affecting health of poultry and indirectly leading to great economic loss among small livestock holders. The prevalence of gastrointestinal helminth parasites in Gallus gallus domesticus was studied from January 2017 to December 2019 in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
2
7
0
2
Order By: Relevance
“…During the study period, the overall prevalence of infection was found to be 49%, signifying that roundworm infection is a common problem in the region and is more or less similar to the prevalence of 45.66%, as reported by Jaiswal et al [ 17 ]. In comparison to the current study, Sreedevi et al [ 18 ] reported a higher frequency (63.21%) in India, and El-Dakhly et al [ 19 ] reported a prevalence of 55.79% in Egypt.…”
Section: Discussionsupporting
confidence: 71%
“…During the study period, the overall prevalence of infection was found to be 49%, signifying that roundworm infection is a common problem in the region and is more or less similar to the prevalence of 45.66%, as reported by Jaiswal et al [ 17 ]. In comparison to the current study, Sreedevi et al [ 18 ] reported a higher frequency (63.21%) in India, and El-Dakhly et al [ 19 ] reported a prevalence of 55.79% in Egypt.…”
Section: Discussionsupporting
confidence: 71%
“…A total of 860 fecal samples were processed and analyzed using direct techniques with ZnSO4 and indirect methods such as modified Sloss [ 11 ], quantified with MacMaster chamber [ 8 , 12 ]. To calculate the frequency of gastrointestinal parasite infection, descriptive statistics using absolute and relative frequency were used.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of parasitic infestations has a high prevalence, causing low economic conditions, increased mortality and prophylaxis, leading to low production, death of animals, and limited productivity. Improved poultry management practices are responsible for the reduction in the incidence of parasitic infections [ 8 ]. Thus, the objective of this work was to identify the prevalence of gastrointestinal parasites in Gallus domesticus , Anas platyrhynchos domesticus , and Meleagris gallopavo managed under the backyard poultry system in the Savanna subregion, Department of Sucre, Colombia.…”
Section: Introductionmentioning
confidence: 99%
“…Nilai prevalensi Helminthiasis dihitung dengan rumus menurut (Jaiswal et al, 2020) sebagai berikut: Nilai Prevalensi = Jumlah sampel terinfeksi/Jumlah sampel yang diuji x 100%…”
Section: Rumus Nilai Prevalensiunclassified
“…Oleh karena itu, Slimane (2016) berpendapat bahwa tindakan tegas harus dilakukan untuk mengendalikan parasit yang penting secara ekonomi ini. Usaha untuk memperbaiki sistem pemeliharaan, sanitasi kandang (Dakpogan et al, 2019), lingkungan yang higienis (Jaiswal et al 2020) menjaga kebersihan tempat pakan dan minum serta pemberian anthelmintik dan dosis yang tepat pada peternakan ayam kampung perlu dilakukan dengan baik dan benar agar prevalensi Helminthiasis dapat ditekan (Iboh, (2019); Uhuo et al, (2013)). Dampak positif dari rendahnya prevalensi Helminthiasis nantinya dapat dirasakan oleh peternak, yaitu memperoleh keuntungan yang optimal.…”
Section: Hasil Dan Pembahasanunclassified